PRAKTEK PERKAWINAN DI BAWAH UMUR MENURUT HUKUM ISLAM DAN HUKUM PERKAWINAN DI INDONESIA - Murni Yanti; Imran Imran; Hendra Surya (AL-ILMU, 2021)
According to Islamic law, what is meant by marriage is a contract that justifies association and limits rights and obligations as well as mutual assistance between a man and a woman who are not between the two of them. "The purpose of marriage is to form a happy and eternal family, for that husband and wife need to help and complement each other, so that each can develop his personality to help and achieve spiritual and material welfare. stipulated age. That is, ideally legally, marriage can take place if the age of the bride and groom has met the requirements of the legislation. The results of the study show that: (1) According to law number 16 of 2019 marriage is only permitted if the male and female parties have reached the age of 19 years (Nineteen years). Islamic law, in this case the Qur'an and hadith do not specifically mention the minimum age for marriage. The general requirements that are commonly known are that they are mature, have common sense, are able to distinguish between good and bad so that they can give their consent to marry. established in the Republic of Indonesia. The impact of education, underage marriage is a factor that hinders the process of education and learning. The psychological impact, from a social perspective, underage marriage can reduce family harmonization. This is caused by emotions that are still unstable, the turmoil of young blood and an immature way of thinking. Biological impact, where the child's reproductive organs are biologically still in the process of reaching maturity so that they are not ready to have sex with the opposite sex, especially if they become pregnant and then give birth. Health impact, women who marry at an early age of less than 15 years have many risks, even though she has experienced menstruation or menstruation.